Genome-Wide Identification and Analysis of Variants in Domestic and Wild Bactrian Camels Using Whole-Genome Sequencing Data - Nemat Hedayat-Evrigh; Reza Khalkhali-Evrigh; Mohammad Reza Bakhtiarizadeh (International Journal of Genomics)
The population size of Bactrian camels is smaller than dromedary, and they are distributed in cold and mountain regions and are also at the risk of extinction in some countries such as Iran. To identify and investigate the genome-wide variations, whole-genome sequencing of two Iranian Bactrian camels were performed with 37.4- and 42.6-fold coverage for the first time. Along with Iranian Bactrian camels, sequencing data from two Mongolian domestic and two wild Bactrian camels deposited in the NCBI were reanalyzed. The analysis eventuated to the identification of 4,908,998, 4,485,725, and 4,706,654 SNPs for Iranian, Mongolian domestic, and wild Bactrian camels, respectively. Also, INDEL variations ranged from 358,311 to 533,188 in all six camels. Results of variants annotation in all samples revealed that more than 88 percent of SNPs and INDELs were located in the intergenic and intronic regions. We found that 800,530 SNPs were common among all studied camels, containing 4,046 missense variants that affected 2,428 genes. Investigation of common genes among all camels containing the missense SNPs showed that there are 98 zinc finger and 4 fertility-related genes (ZP1, ZP2, ZP4, and ZPBP) in this set.